Evaluation of biochemical markers effectiveness in elderly malnutrition assessment - Larisa Gavran; Jelena Pavlović; Maja Račić; Nedeljka Ivković; Ksenija Tušek Bunc (Medicinski glasnik, 2019)
Aim: To systematically review the scientific evidence of biomarker validity, reliability, specificity and sensitivity in identifying malnutrition in the elderly. Methods: Peer-reviewed journals were searched using PUBMED and EBSCO from January 1998 to April 2018. The articles included description of the association between malnutrition blood biomarkers and validated nutritional status assessment instruments and studies were conducted among community-dwelling elderly or nursing home residents. Results: The research strategy identified a total of 293 studies. This literature review picked out seven articles for follow-up evaluation. A total of sixteen blood biomarkers were identified. Six studies found a significant association between the nutritional assessment score and albumin level. Conclusion: Combining serum concentrations of malnutrition biomarkers with nutritional status assessment tools has a great potential in identifying the risk of malnutrition in the elderly, while also increasing sensitivity and specificity.
Keywords: aged; biomarkers; geriatric assessment; humans; malnutrition